Reviews. Issue 4 (1st October 2016) - Ashmore, Beth; Moreno, Heylicken; Parang, Elizabeth
ABSTRACT: Heylicken Moreno reviews FRBR, Before and After: A Look at our Bibliographic Models ; Elizabeth Parang reviews The Librarian's Nitty-Gritty Guide to Content Marketing .